Microbiota-Modulated Metabolites Shape the Intestinal Microenvironment by Regulating NLRP6 Inflammasome Signaling - Levy, Maayan; Thaiss, Christoph A.; Zeevi, David; Dohnalová, Lenka; Zilberman-Schapira, Gili; Mahdi, Jemal Ali; David, Eyal; Savidor, Alon; Korem, Tal; Herzig, Yonatan; Pevsner-Fischer, Meirav; Shapiro, Hagit; et al. (Cell, 2015)
Host-microbiome co-evolution drives homeostasis and disease susceptibility, yet regulatory principles governing the integrated intestinal host-commensal microenvironment remain obscure. While inflammasome signaling participates in these interactions, its activators and microbiome-modulating mechanisms are unknown. Here, we demonstrate that the microbiota-associated metabolites taurine, histamine, and spermine shape the host-microbiome interface by co-modulating NLRP6 inflammasome signaling, epithelial IL-18 secretion, and downstream anti-microbial peptide (AMP) profiles. Distortion of this balanced AMP landscape by inflammasome deficiency drives dysbiosis development. Upon fecal transfer, colitis-inducing microbiota hijacks this microenvironment-orchestrating machinery through metabolite-mediated inflammasome suppression, leading to distorted AMP balance favoring its preferential colonization. Restoration of the metabolite-inflammasome-AMP axis reinstates a normal microbiota and ameliorates colitis. Together, we identify microbial modulators of the NLRP6 inflammasome and highlight mechanisms by which microbiome-host interactions cooperatively drive microbial community stability through metabolite-mediated innate immune modulation. Therefore, targeted “postbiotic” metabolomic intervention may restore a normal microenvironment as treatment or prevention of dysbiosis-driven diseases. [Display omitted] •Microbiota-modulated metabolites regulate NLRP6 inflammasome and intestinal IL-18•Inflammasome-derived IL-18 orchestrates colonic anti-microbial peptide expression•Inflammasome modulation by metabolites enables dysbiotic community transfer•Integrated metabolite signaling determines the severity of intestinal inflammation Microbiota-associated metabolites shape the host-microbiome interface by modulating NLRP6 inflammasome signaling, epithelial IL-18 secretion, and the generation of downstream anti-microbial peptides. This axis, therefore, determines both host indigenous microbiome profiles and the susceptibility to intestinal inflammation.